Incorporation of Invited Lectures in the English Development and Engagement course: A Review of Students’ Readiness and Acceptance - Ang, Peniel Soon Ern; Chan, Chee Ming (Progress in Engineering Application and Technology, 2023)
It was compulsory for Year 1 Engineering Technology students to undertake the English Development & Engagement course, designated to hone the students’ language skills in both written and oral forms. For enhancing the international outreach of the course, invited lectures were incorporated with the participation of a couple of English lecturers from Indonesia for the topics of presentation skills and vlogging. A brief survey was next conducted to gauge the students’ readiness and acceptance of the new practice. From the general feedback, learning impact and way forward inputs, students apparently enjoyed the cross-national learning experience with an effective exploration of the language skills, styles and expressions. The sessions were also found to raise students’ awareness and skills in using English as a tool for work organization and communication in a teamwork environment. Indeed students requested to have more such sessions with interactive activities, learning games as well as instant reviews to enable higher order of relevant knowledge and skills retention.